Modified ceramic tubular membrane as well as preparation method and application thereof
By depositing a composite material with nickel-iron layered bimetallic hydroxide-loaded SnO2 nanoparticles on the surface of the ceramic tube film, the problems of insufficient catalytic activity of the ceramic film and high membrane pollution rate are solved, and more efficient catalytic ozone oxidation and The filtration effect reduces membrane pollution, improves treatment efficiency and anti-pollution ability.
Patent Information
- Application Number
- CN202411544766.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing ceramic membranes lack catalytic activity in catalytic ozone oxidation treatment, and the modification method is difficult to take into account both catalytic and filtration functions, resulting in difficult to fully exert synergy effects and high membrane pollution rate.
Ni-iron layered bimetallic hydroxide (Ni-Fe LDH) is deposited on the surface of ceramic tubular films and supported on SnO2 nanoparticles to form Ni-Fe LDH/SnO2 composite material as a catalytic layer, and the film is modified by coating. surface, improve catalytic performance and filtration performance.
The film surface properties, interception and catalytic properties are significantly improved, the ozone catalytic activity is enhanced, the membrane pollution rate is reduced, the pollutant treatment efficiency and anti-pollution ability are improved, and the flux changes in the modified membrane during long-term operation are smooth.
Smart Images

Figure CN119113823A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a modified ceramic tubular membrane and a preparation method thereof, and the modified ceramic tubular membrane is applied to catalytic ozone oxidation-membrane filtration coupling treatment of polluted water, belonging to the technical field of ozone catalytic oxidation and water treatment. Background Art
[0002] Membrane filtration technology is an advanced means of deep water treatment. It can achieve molecular-level filtration through the selective separation of membrane materials under the driving force of pressure, concentration, etc. Among various membrane materials, ceramic membrane (CM), which belongs to the inorganic membrane category, can maintain long-term stable operation under extremely polluted conditions due to its high mechanical strength, high thermal stability and good chemical stability. In recent years, its related research and application have become increasingly extensive. However, the single separation function and the membrane pollution problem caused by the accumulation of pollutants in the water treatment process have limited the further application of CM.
[0003] Combining ozone oxidation with CM filtration can produce a synergistic effect, thereby effectively improving the above problems. In the combined process, CM materials catalyze ozone oxidation to generate active species such as hydroxyl radicals through metal redox and surface hydroxyl conversion, which not only further improves the pollutant treatment efficiency under the collaborative filtration effect, but also significantly reduces the membrane fouling rate. It can be seen that the activity of CM catalytic ozone is one of the key factors affecting the treatment effect of CM filtration-ozone catalytic oxidation and controlling the degree of membrane fouling. Studies have proposed that high-activity components can be loaded on CM by coating, doping, sintering, etc., and functional modification can be carried out with the goal of improving the catalytic performance of the membrane.
[0004] The invention with publication number CN117797658A provides a ceramic membrane with a catalytic ozone oxidation functional layer, and the catalytic coating is prepared by preparing a manganese oxide slurry coating liquid. The invention with publication number CN117225202A provides a method for preparing a catalytic ozonation Mn-alkaline earth metal / ceramic membrane, which improves the activity of catalytic ozonation treatment of organic wastewater. However, in the current research on metal-modified CM, there are still some shortcomings that need to be overcome and improved: First, from the perspective of the ozone catalytic oxidation mechanism, the constructed high-activity components still have room for further optimization and regulation in promoting electron transfer for redox reactions; second, some modification methods cannot take into account both catalytic and filtration functions, resulting in the synergistic effect being difficult to fully exert. Therefore, it is necessary to study more efficient CM materials. Summary of the invention
[0005] In order to solve the problems of the prior art, the present invention provides a modified ceramic tubular membrane and a preparation method and application thereof. In the present invention, nickel-iron layered double hydroxide (Ni-Fe LDH) is loaded on SnO 2 Ni-FeLDH / SnO nanoparticles2 and coated on the surface of ceramic tubular membrane (CM) as a reinforced catalytic layer. 2 The composite material is a highly active component of ozone catalysis and is used to modify the ceramic tubular membrane in a coating manner, so that the membrane surface properties, membrane retention rate and catalytic performance are significantly improved.
[0006] The technical solution of the present invention is as follows:
[0007] One of the purposes of the present invention is to provide a modified ceramic tubular membrane, wherein a composite catalyst layer is deposited on the surface of the ceramic tubular membrane; the composite catalyst layer is composed of SnO loaded with nickel-iron layered double metal hydroxide. 2 Nanoparticle composition.
[0008] Furthermore, the nickel-iron layered double metal hydroxide and SnO in the composite catalyst layer 2 The mass ratio is (1~3):1.
[0009] The second object of the present invention is to provide a method for preparing the above-mentioned modified ceramic tubular membrane, which comprises the following steps:
[0010] S1. Preparation of SnO 2 Nanoparticles: NaOH solution was slowly added to the aqueous solution containing tin source to adjust the solution pH to 9, and the solution was continuously stirred at room temperature until a yellow / white gel appeared; the gel was washed with a mixed solution of distilled water and ethanol, dried and dehydrated, and calcined at 550°C to obtain SnO 2 Nanoparticles;
[0011] S2, nickel-iron layered double hydroxide loading: SnO 2 Nanoparticles were added to the solution of Ni(NO 3 ) 2 6H 2 O, Fe(NO 3 ) 3 9H 2 O metal salt solution, dropwise addition of NaOH and Na 2 CO 3 The alkaline solution was stirred for at least 2 h; the solution was then transferred to a Teflon-lined autoclave and reacted at 120 °C for 6 h. The sample was centrifuged, washed, and dried to obtain SnO 2 Supporting nickel-iron layered double hydroxide composite;
[0012] S3. Composite catalytic layer deposition: SnO 2 The loaded nickel-iron layered double hydroxide complex is dispersed in water to obtain a complex suspension; the complex suspension is prepared by Figure 1The device shown is sprayed on the surface of a ceramic tubular membrane to deposit under the drive of nitrogen at least 0.3MPa to form a composite catalytic layer. The catalytic layer is deposited 1 to 3 times according to the same method to adjust the coating thickness; then the obtained ceramic tubular membrane is vacuum dried and cured at 50°C for at least 24 hours to obtain the modified ceramic tubular membrane.
[0013] Furthermore, the tin source in step S1 is crystalline tin tetrachloride (SnCl 4 ), the dosage of tin source is 0.02g / mL.
[0014] Furthermore, in step S1, the ratio of the distilled water and ethanol mixed washing solution is 1:1; and the gel is calcined at 550° C. for preferably 2 h.
[0015] Furthermore, the metal ion concentration of the metal salt solution in step S2 is 0.54 mol / L, Ni(NO 3 ) 2 6H 2 O and Fe(NO 3 ) 3 9H 2 The molar ratio of O is 3:1; the composition of the alkaline solution is: 1.2 mol / L NaOH and 0.32 mol / L Na 2 CO 3 The volume ratio of the added amount of alkaline solution to the metal salt solution is 1:1.
[0016] Furthermore, the nickel-iron layered double hydroxide Ni-Fe LDH and SnO 2 The mass ratio is (1~3):1.
[0017] Furthermore, the CM used in step S3 is a commercial membrane made of α-Al 2 O 3 Support layer and ZrO 2 Filter layer composition; the total filtration area of the CM is 0.00133m 2 (Inner dimensions are 25.4 mm (diameter) x 100 mm (height)), and the average pore size is 100 nm.
[0018] Furthermore, in step S3, SnO 2 The dosage of the loaded nickel-iron layered double hydroxide composite is 0.2 g / L.
[0019] The third object of the present invention is to apply the modified ceramic tubular membrane to the catalytic ozone oxidation-membrane filtration coupling treatment of mixed dye-contaminated water.
[0020] The present invention also provides a treatment process for mixed dye-contaminated water, comprising the following steps: mixing ozone water with mixed dye-contaminated water, wherein the volume ratio of ozone water to mixed dye-contaminated water is 1:1; and then passing the mixed contaminated water through a modified ceramic tubular membrane reactor at a flow rate of 20 mL / min to perform catalytic ozone oxidation to degrade the mixed dye.
[0021] Furthermore, the pollutants in the mixed dye-polluted water may be one or more of Rhodamine B, Acid Blue 92 and Malachite Green 92.
[0022] Different from the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention proposes to prepare a modified ceramic tubular membrane by depositing a composite catalyst layer on the surface of a ceramic tubular membrane, wherein the composite catalyst layer is Ni-Fe LDH / SnO 2 The composite catalyst layer has low surface roughness, adjustable catalyst layer thickness and excellent anti-pollution ability. The nanoparticles are attached to the surface of the ceramic membrane, and the microstructure (particle size, pore size and porosity) and performance (hydrophilicity and stability) of the membrane surface are improved. At the same time, the Ni-Fe LDH / SnO 2 The ceramic membrane modified by the composite catalytic layer has the functions of photosensitization and sterilization, which can further improve the treatment effect of the catalytic ozone oxidation filtration combined process and reduce the degree of membrane pollution;
[0024] 2. The present invention also provides a Ni-Fe LDH / SnO 2 In order to enhance the catalytic ozone oxidation membrane filtration process of catalytic layer modified ceramic tubular membrane, Ni-Fe LDH / SnO was loaded on the surface of the ceramic membrane filtration layer using the ceramic membrane as a carrier. 2 After the heterojunction composite structure, two pairs of redox pairs (Ni 2+ / Ni 3+ and Fe 2+ / Fe 3+ ) and the synergistic effect of SnO 2 The presence of SnO enhances the electron transfer ability. 2 The surface is rich in hydroxyl groups, which further accelerates the decomposition of ozone and forms active oxygen species, degrading the macromolecules deposited on the membrane surface into small molecules, or even directly degrading them into CO 2 and H 2 O;
[0025] 3. After catalytic ozone oxidation membrane filtration process and characterization test, the ceramic tubular membrane modified by the enhanced catalytic layer of the present invention has an improved removal rate of mixed pollutants by about 20% to 30% compared with the unmodified ceramic membrane when the pollutants and ozone water have a flow rate of 20 mL / min, an ozone concentration of 4 mg / L, and a mixed pollutant concentration of 50 mg / L after 1 hour of reaction. In addition, the membrane flux changes smoothly during long-term operation, which proves that the catalytic membrane has excellent ozone catalytic ability and anti-membrane pollution ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Deposition of Ni-Fe LDH / SnO for the preparation of modified ceramic membranes 2 Device of composite catalytic layer.
[0027] Figure 2 The SEM images and properties of different materials are compared, where (a) is SnO 2 SEM images of Ni-Fe LDH:SnO 2 Ni-Fe LDH / SnO with a mass ratio of 2:1 2 SEM images of the composite catalytic layer. Figure (d) shows different mass ratios of Ni-Fe LDH / SnO 2 XRD patterns of the composite catalyst layer. Figure (e) shows the XRD patterns of Ni-Fe LDH / SnO with different mass ratios. 2 Composite catalytic layer and SnO 2 Figure (f) shows the degradation rate constant of RhB of Ni-Fe LDH / SnO at different mass ratios. 2 Composite catalytic layer and SnO 2 , Ni-Fe LDH corresponding to COD removal rate.
[0028] Figure 3 Surface and cross-sectional SEM images of the original ceramic membrane and the modified ceramic membrane, where (a, e) is CM, (b, f) is NFS-1 / CM, (c, g) is NFS-2 / CM, and (d, h) is NFS-3 / CM.
[0029] Figure 4 AFM images of the original ceramic membrane and the modified membrane, where (a) is CM, (b) is NFS-1 / CM, (c) is NFS-2 / CM, and (d) is NFS-3 / CM.
[0030] Figure 5 Contact angle measurements of the original ceramic membrane and the modified membrane, where Figure (a) is CM, Figure (b) is NFS-1 / CM, Figure (c) is NFS-2 / CM, and Figure (d) is NFS-3 / CM.
[0031] Figure 6 The removal effect of the original ceramic membrane and the modified membrane on mixed dyes (a) and COD removal rate (b).
[0032] Figure 7 Effects of HA on the removal efficiency of mixed dyes by NFS-2 / CM (a) and normalized membrane flux (b).
[0033] Figure 8 To illustrate the stability of the modified membrane: (a) membrane flux, (b) membrane flux recovery with different cleaning agents.
[0034] Fig. 9 High-resolution XPS spectra of NFS-2 / CM before and after catalytic ozonation and electrochemical impedance spectra of different materials, where (a) is the Fe 2p XPS spectrum, (b) is the Ni 2p XPS spectrum, (c) is the O1s XPS spectrum, (d) is the Sn 3d XPS spectrum, and (e) is the electrochemical impedance spectrum. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with the accompanying drawings and preferred embodiments. The given embodiments are only for illustrating the present invention, rather than for limiting the scope of the present invention.
[0036] Unless otherwise specified, the materials, reagents, etc. used in the following examples can be obtained from commercial sources; the methods in the following examples are conventional methods unless otherwise specified.
[0037] Example 1
[0038] This embodiment provides a modified ceramic tubular membrane, on the surface of which a composite catalyst layer is deposited; the composite catalyst layer is composed of SnO loaded with nickel-iron layered double metal hydroxide. 2 The composite catalyst layer is composed of nickel-iron layered double metal hydroxide Ni-Fe LDH and SnO 2 The mass ratio of the composite catalyst layer is 3:1; the coating frequency of the composite catalyst layer is 1 time.
[0039] The preparation method of the modified ceramic tubular membrane comprises the following steps:
[0040] S1. Preparation of SnO 2 Nanoparticles: 1gSnCl 4Dissolve in 50 mL of distilled water, stir magnetically at room temperature for 30 min, slowly add 6 M NaOH solution to adjust the pH to 9, and continue stirring at room temperature for 12 h until a yellow / white gel is obtained; the obtained gel is centrifuged at 5000 rpm for 5 min, and then washed three times with a mixed solution of distilled water: ethanol 50:50 v / v to remove undissolved particulate impurities. The purified gel is dried at 80 ° C for 24 h, then ground and calcined at 550 ° C for 2 h, with a heating rate of 4 ° C / min, to obtain SnO 2 Nanoparticles;
[0041] S2, loading nickel-iron layered double hydroxide: 0.4 g SnO 2 The nanoparticles were added to 25 mL of 10.125 mmol Ni(NO 3 ) 2 6H 2 O and 3.375mmol Fe(NO 3 ) 3 9H 2 O metal salt solution, and then add 25mL of 0.03mol NaOH and 0.008mol Na 2 CO 3 The alkaline solution was stirred for 2 h; the solution was then transferred to a Teflon-lined autoclave and reacted at 120 °C for 6 h. The reactant was centrifuged, washed, and dried to obtain Ni-Fe LDH / SnO 2 Complex;
[0042] S3, composite catalyst layer deposition: 0.2g Ni-Fe LDH / SnO 2 The complex was added to 1L of deionized water and dispersed by ultrasonication for 30min. Figure 1 The device shown in the figure is driven by nitrogen at 0.3 MPa and sprayed on the surface of the ceramic tubular membrane to form Ni-Fe LDH / SnO 2 The composite catalytic layer was coated once, and then the obtained modified membrane was vacuum dried and cured at 50° C. for 24 hours to obtain a modified ceramic tubular membrane.
[0043] Example 2
[0044] This embodiment provides a modified ceramic tubular membrane, which is different from Embodiment 1 in that:
[0045] The nickel-iron layered double hydroxide Ni-Fe LDH and SnO 2 The mass ratio is 2:1.
[0046] The preparation method of the modified ceramic tubular membrane is different from that of Example 1 in that:
[0047] SnO in step S2 2 The amount of nanoparticles added was 0.6 g.
[0048] The number of coatings of the composite catalyst layer is the same as that in Example 1, and SnO 2 The steps for preparing the nanoparticles and depositing the composite catalytic layer are the same as those in Example 1 and will not be described in detail here.
[0049] Example 3
[0050] This embodiment provides a modified ceramic tubular membrane, which is different from Embodiment 1 in that:
[0051] The nickel-iron layered double hydroxide Ni-Fe LDH and SnO 2 The mass ratio is 1:1.
[0052] The preparation method of the modified ceramic tubular membrane is different from that of Example 1 in that:
[0053] SnO in step S2 2 The amount of nanoparticles added was 1.2 g.
[0054] The number of coatings of the composite catalyst layer is the same as that in Example 1, and SnO 2 The steps for preparing the nanoparticles and depositing the composite catalytic layer are the same as those in Example 1 and will not be described in detail here.
[0055] Example 4
[0056] This embodiment provides a method for preparing a modified ceramic tubular membrane, which is different from that of embodiment 1 in that:
[0057] The composite catalytic layer is coated twice.
[0058] The preparation method of the modified ceramic tubular membrane is different from that of Example 1 in that:
[0059] The coating times of the composite catalytic layer in step S3 is 2 times.
[0060] Nickel-iron layered double hydroxide Ni-Fe LDH and SnO in the composite catalyst layer 2 The mass ratio of SnO is the same as that in Example 1. 2 The steps of preparing the nanoparticles and loading the nickel-iron layered double hydroxide are the same as those in Example 1 and will not be described again.
[0061] Example 5
[0062] This embodiment provides a method for preparing a modified ceramic tubular membrane, which is different from that of embodiment 1 in that:
[0063] The composite catalytic layer is coated three times.
[0064] The preparation method of the modified ceramic tubular membrane is different from that of Example 1 in that:
[0065] The number of coating times of the composite catalytic layer in step S3 is 3 times.
[0066] Nickel-iron layered double hydroxide Ni-Fe LDH and SnO in the composite catalyst layer 2 The mass ratio of SnO is the same as that in Example 1. 2 The steps of preparing the nanoparticles and loading the nickel-iron layered double hydroxide are the same as those in Example 1 and will not be described again.
[0067] Performance Testing
[0068] (1) Ni-Fe LDH / SnO modified ceramic tubular membrane 2 Physicochemical properties of the catalyst layer
[0069] The different Ni-Fe LDH:SnO 2 Mass ratio of Ni-Fe LDH / SnO modified ceramic tubular membrane 2 The composite catalyst layer was subjected to SEM, XRD and ozone oxidation performance tests to study the Ni-Fe LDH / SnO 2 Physicochemical properties of the composite catalytic layer.
[0070] SnO 2 and Ni-Fe LDH / SnO 2 The SEM images are as follows Figure 2 As shown in a~c, SnO 2 The morphology is a square particle with a smooth surface and a large nanometer size. 2 The surface is covered with a layer of Ni-Fe LDH, which is well distributed on the surface. Figure 2 d is different Ni-Fe LDH:SnO 2 Mass ratio Ni-Fe LDH / SnO 2 XRD patterns of composite materials with different mass ratios of Ni-Fe LDH / SnO 2 The composites showed clear Ni-Fe LDH and SnO 2 The diffraction peaks show that the composite catalytic layer is composed of Ni-Fe LDH and SnO 2 constitute.
[0071] For different mass ratios of Ni-Fe LDH / SnO 2The catalytic ozone oxidation and degradation performance of dye pollutants of the composite catalytic layer were evaluated. Rhodamine B (RhB) was used as the water pollutant. The experiment was carried out according to the following steps: Ni-Fe LDH / SnO 2 The complex was added to a conical reactor containing 400 mL of RhB solution and stirred for 30 min to reach adsorption / desorption equilibrium, and then gaseous ozone was introduced into the reactor from the ozone generator. 2 Complex dosage = 0.5 g / L, RhB concentration = 50 mg / L, ozone flow rate = 50 mg / h, pH = 8.
[0072] The results of the performance evaluation are as follows: Figure 2 As shown in e and f, compared with the same amount of SnO 2 Unlike Ni-Fe LDH, Ni-FeLDH:SnO 2 Mass ratio of Ni-Fe LDH / SnO 2 The catalytic ozone reaction rate and COD removal rate of the composite catalytic layer were significantly improved, showing a high catalytic ozone activity. 2 The mass ratio increases from 1 to 3, Ni-Fe LDH / SnO 2 The degradation of RhB in the composite catalytic layer gradually increased, and the reaction rate increased to 0.059min -1 , the final COD removal rate is close to 90%.
[0073] In summary, different Ni-Fe LDH:SnO 2 Mass ratio of Ni-Fe LDH / SnO 2 The composite catalytic layer has similar physical and chemical properties, and both show high catalytic ozone activity and high COD removal rate. 2 As the mass ratio is improved, the catalytic ozone activity of the catalytic layer is also improved.
[0074] (2) Physical and chemical properties of modified ceramic membranes
[0075] SEM and AFM were used to characterize the modified ceramic membranes of different film thicknesses in the above-mentioned Examples 1, 4 and 5. According to the number of coatings, the samples were named NFS-1 / CM, NFS-2 / CM and NFS-3 / CM, respectively.
[0076] Figure 3 a~d are surface SEM images of the original ceramic membrane (CM) and the modified ceramic membranes NFS-1 / CM, NFS-2 / CM and NFS-3 / CM with different catalytic layer thicknesses. Compared with the modified membranes, the pore structure of CM is clearly visible. As the number of coatings increases, the Ni-FeLDH / SnO2 It continuously covers the pores in the membrane, and the membrane surface becomes denser. Figure 3 e~h are cross-sectional SEM images of CM and modified membrane. The layered structure of the modified membrane is distinct, from bottom to top, including support layer Al 2 O 3 , Filter layer ZrO 2 and catalyst layer Ni-Fe LDH / SnO 2 .Ni-Fe LDH / SnO 2 There is a certain linear relationship between the number of coatings and their thickness. The thickness of coating once, twice and three times are 18, 26 and 35 μm respectively.
[0077] The surface roughness of CM and modified membranes was analyzed by AFM, such as Figure 4 The roughness parameters of each sample are calculated based on the scanning area of 5.0 μm × 5.0 μm. It can be clearly seen that the modified film is smoother than CM. 2 As the number of coatings increases, the roughness decreases from 256nm to 76.7nm. This is because Ni-Fe LDH / SnO 2 The particles filled the pores in the filtration layer and reduced the hills on the membrane surface, which is consistent with the previous SEM observation results. The surface hydrophilicity of CM and modified membranes was analyzed by contact angle measurement, such as Figure 5 As shown. With Ni-Fe LDH / SnO 2 With the increase of coating times, the hydrophilicity of the modified membrane surface gradually increased, and the contact angle gradually decreased from 79.74±1.52° to 13.17±0.32°.
[0078] In general, the modified ceramic tubular membranes of the present invention all exhibit relatively high hydrophilicity. Compared with the original CM, the modified ceramic tubular membranes are smoother than the original CM, which helps to reduce the accumulation of pollutants on the membrane surface and alleviate certain membrane pollution, and is more conducive to the water treatment application of membrane materials; at the same time, with the increase of membrane thickness, the hydrophilicity of the modified membrane surface is gradually enhanced, and the catalytic layer of sufficient thickness can provide more reaction active sites to activate ozone.
[0079] (3) Efficiency of modified membrane catalytic ozone oxidation-filtration treatment of dye pollutants
[0080] In order to elaborate on the performance of the modified ceramic tubular membrane of the present invention in catalytic ozone oxidation and filtration of dye pollutants, taking the treatment of mixed dye-contaminated water containing pollutants such as rhodamine B (RhB), acid blue (MG), malachite green 92 (AB92) as an example, NFS-1 / CM, NFS-2 / CM, and NFS-3 / CM were applied to catalytic ozone oxidation-membrane filtration coupling treatment of mixed dye-contaminated water, and the experiment was carried out according to the following steps:
[0081] S1. Modified ceramic tubular membrane ozone catalytic reaction: use an ozone generator to pass into a 1.5L water tank at a flow rate of 300mL / min to dissolve and pre-mix the gas and water to obtain ozone water, and use an ozone detector to monitor the dissolved ozone concentration; prepare the mixed dye-contaminated water in the original water tank; use a peristaltic pump to simultaneously deliver the ozone water and the mixed dye-contaminated water into the membrane reactor at a volume ratio of 1:1 at a flow rate of 20mL / min for catalytic ozone oxidation degradation;
[0082] The pollutants in the mixed dye-contaminated water include: rhodamine B (RhB), acid blue (MG), malachite green 92 (AB92);
[0083] S2. Water quality detection: Water flows from the inside to the outside of the composite membrane, and samples are drawn from the sampling port at a certain reaction time for subsequent analysis. Before analysis, the samples are filtered through a microfiber filter with a pore size of 0.45μm. During the water delivery process, hydraulic time control is performed by changing the pump speed, and the pressure on the inlet and outlet sides of the membrane reactor is automatically monitored to calculate the TMP. At the same time, the amount of purified water outlet is recorded, and the change in membrane flux at the corresponding time is calculated. The residual concentration (Ct) of RhB, MG, and AB92 is measured by measuring the absorbance changes at 554nm, 572nm, and 618nm with an ultraviolet spectrophotometer, and the degradation efficiency of mixed dye pollutants is comprehensively evaluated. COD removal is determined using the national standard dichromate method.
[0084] The concentrations of RhB, MG, and AB92 in the mixed dye-contaminated water treated with different samples in the experiment were the same; the concentration of ozone water used in different samples in the experiment was 4 mg / L.
[0085] The experimental results are as follows:
[0086] Figure 6 a and b are the removal efficiency of mixed dyes by different modified ceramic tubular membranes and their COD removal rates. The reaction conditions are: the volume ratio of mixed dye-contaminated water to ozone water is 1:1, the inflow flow rate is 20mL / min, the ozone is 4mg / L, and the mixed dyes are 5mg / L, 5mg / L, and 5mg / L of RhB, MG, and AB92. CM only removes about 60% of the mixed dyes within 60 minutes, while the relative NFS-1 / CM, NFS-2 / CM, and NFS-3 / CM reach about 80%, 85%, and 90% removal rates, respectively, which are significantly improved. In terms of COD removal, there are also significant differences between different membrane materials, indicating that the presence of the catalytic layer promotes the catalytic ozone oxidation process, provides stronger oxidation capacity, and enables the effective degradation and mineralization of dye pollutants.
[0087] Humic acid (HA), as one of the typical components of natural organic matter (NOM), like inorganic ions, significantly affects the treatment effect in the actual sewage treatment process. Figure 7 a is the effect of different HA dosage on NFS-2 / CM treatment of mixed dyes. The reaction conditions are: the volume ratio of mixed dye contaminated water to ozone water is 1:1, the inflow flow rate is 20mL / min, the ozone is 4mg / L, the mixed dyes RhB 5mg / L, MG 5mg / L, AB92 5mg / L. The results show that as the HA concentration increases from 15ppm to 60ppm, the removal rate of mixed pollutants decreases from 80% to 65%. At the same time, due to the large molecular structure of HA, in addition to affecting the removal of target pollutants, it also significantly affects the membrane flux. Figure 7 As shown in Figure b, when the HA concentration is 15ppm, the normalized membrane flux of NFS-2 / CM decreases from 80% to 60%, which is higher than 45% of CM, indicating that the enhancement of active species generation by ozone catalytic oxidation can effectively convert large molecular organic matter such as HA into smaller molecular products, thus alleviating membrane fouling behavior. However, when the HA concentration is high, HA not only inhibits ozone catalytic oxidation, but also accumulates on the membrane surface, thereby aggravating the membrane fouling.
[0088] The change trend of membrane flux and pollutant removal performance of modified ceramic tubular membrane under long-term operation is as follows Figure 8 As shown in a, the reaction conditions are: the feed flow rate is 20 mL / min, the feed liquid and O 3 (aq) water volume ratio is 1:1, RhB = 5 mg / L, AB92 = 5 mg / L, MG = 5 mg / L, HA = 15 mg / L, O 3 (aq) = 4 mg / L. Due to the presence of the catalytic layer, the modified membrane exhibits excellent performance in resisting membrane fouling. After running for 300 min, it can still maintain 60% of the normalized membrane flux. Two cleaning methods were studied after the cycle experiment. One is to replace the pollutants with deionized water in the modified membrane after use and run it under the same experimental conditions for 30 minutes. The other is to use ozone aqueous solution under the same conditions. Figure 8 As shown in Figure b, after washing with deionized water, NFS-2 / CM and CM recovered to 80% and 60% of the initial membrane flux, respectively, while after washing with ozone aqueous solution, the membrane flux recovered to 88% and 65%. This may be because the HA coated on the surface was decomposed by ozone during the ozone water cleaning process, breaking down the high molecular weight HA molecules into smaller fragments, allowing them to pass through the membrane pores, and at the same time, the hydrophobic part of HA was converted into a hydrophilic reaction product.
[0089] In order to further explore the mechanism of catalytic ozone oxidation of modified ceramic tubular membranes, XPS analysis was performed on the chemical composition and valence changes of NFS-2 / CM modified ceramic tubular membranes before and after catalytic ozone oxidation. Fig. 9As shown in a, in Fe 2p 3 / 2 In the peak fitting of , Fe mainly exists in the form of multivalent states. After the reaction, Fe 3+ The proportion of Fe 2+ During the reaction, it is partially oxidized to Fe 3+ . Fig. 9 b is Ni 2p spectrum, Ni before and after the reaction 2+ The change in the proportion indicates that Ni ions serve as the main active sites in the ozone catalytic oxidation process and exist on the catalyst surface in a multivalent state to participate in the reaction. 2 The surface is rich in hydroxyl groups and can accelerate the decomposition of ozone and form active oxygen species. In the O1s spectrum ( Fig. 9 c), the binding energy of 531.4 eV represents the hydroxyl functional group (M-OH). After the reaction, the surface hydroxyl content increased from 50% to 68%, indicating that there is an interaction between the hydroxyl groups on the metal surface and ozone. Fig. 9 d is the Sn 3d spectrum, the binding energies are 486.5eV and 494.9eV respectively, and there is no obvious change before and after the reaction, indicating that SnO 2 Finally, from Fig. 9 e can be seen, compared with the pure SnO 2 Compared with NiFe-LDH, Ni-Fe LDH / SnO 2 The arc radius is relatively small, indicating that the charge migration resistance is reduced, which is conducive to electron transfer. Therefore, in the reaction system, the synergistic effect of the two redox pairs enhances the electron transfer ability and accelerates the occurrence of redox reactions; SnO 2 The resistance of Ni-Fe LDH decreases after doping, indicating that the resistance of electron transfer is small. 2 The surface is rich in hydroxyl groups, which can further accelerate the decomposition of ozone and form reactive oxygen species.
Claims
1. A modified ceramic tubular membrane, It is characterized in that The surface of the ceramic tubular membrane is deposited with a composite catalyst layer; the composite catalyst layer is composed of SnO loaded with nickel-iron layered double metal hydroxide 2 Nanoparticle composition.
2. A modified ceramic tubular membrane according to claim 1, It is characterized in that The nickel-iron layered double metal hydroxide and SnO 2 The mass ratio is (1~3):
1.
3. A method for preparing a modified ceramic tubular membrane, It is characterized in that The steps include: S1. Preparation of SnO 2 Nanoparticles: Slowly add NaOH solution to the aqueous solution containing crystalline tin tetrachloride to adjust the pH of the solution to 9. The solution is continuously stirred at room temperature until a yellow / white gel appears. The gel was washed, dried and dehydrated, and calcined at 550°C to obtain SnO 2 Nanoparticles; S2, nickel-iron layered double hydroxide loading: SnO 2 Nanoparticles were added to the solution of Ni(NO 3 ) 2 6H 2 O, Fe(NO 3 ) 3 9H 2 O metal salt solution, dropwise addition of NaOH and Na 2 CO 3 of alkaline solution and continue stirring for at least 2h; The solution was then transferred to an autoclave and reacted at 120 °C for 6 h. The sample was centrifuged, washed, and dried to obtain SnO 2 Supporting nickel-iron layered double hydroxide composite; S3. Composite catalytic layer deposition: SnO 2 The loaded nickel-iron layered double hydroxide complex is dispersed in water to obtain a complex suspension; The composite suspension is sprayed on the surface of the ceramic tubular membrane under a nitrogen pressure of at least 0.3 MPa to form a composite catalytic layer. The catalytic layer is deposited 1 to 3 times according to the same method to adjust the coating thickness; the obtained ceramic tubular membrane is then vacuum dried and cured at 50°C for at least 24 hours to obtain the modified ceramic tubular membrane.
4. A method for preparing a modified ceramic tubular membrane according to claim 3, It is characterized in that The concentration of tin in the aqueous solution containing the tin source in step S1 is 0.02 g / mL.
5. The method for preparing a modified ceramic tubular membrane according to claim 3, It is characterized in that The metal ion concentration of the metal salt solution in step S2 is 0.54 mol / L, Ni(NO 3 ) 2 6H 2 O and Fe(NO 3 ) 3 9H 2 The molar ratio of O is 3:
1.
6. A method for preparing a modified ceramic tubular membrane according to claim 3, It is characterized in that The composition of the alkaline solution is: 1.2 mol / L NaOH and 0.32 mol / L Na 2 CO 3 The volume ratio of the added amount of alkaline solution to the metal salt solution is 1:
1.
7. The method for preparing a modified ceramic tubular membrane according to claim 3, It is characterized in that The nickel-iron layered double hydroxide and SnO in the composite in step S2 2 The mass ratio is (1~3):
1.
8. The method for preparing a modified ceramic tubular membrane according to claim 3, It is characterized in that SnO in the composite suspension in step S3 2 The dosage of the loaded nickel-iron layered double hydroxide composite is 0.2 g / L.
9. Use the modified ceramic membrane described in any one of claims 1 to 2 or the modified ceramic tubular membrane prepared by the method described in any one of claims 3 to 8 to treat mixed dye-contaminated water by catalytic ozone oxidation-membrane filtration coupling.
10. A process for treating water contaminated by mixed dyes. It is characterized in that The steps include: Ozone water is mixed with mixed dye-contaminated water, and the volume ratio of ozone water to mixed dye-contaminated water is 1:1; then the mixed contaminated water is passed through a reactor loaded with a modified ceramic membrane as described in any one of claims 1 to 2 or a modified ceramic tubular membrane prepared by the method as described in any one of claims 3 to 8 at a flow rate of 20 mL / min to perform catalytic ozone oxidation degradation of the mixed dye-contaminated water.
Citation Information
Patent Citations
Preparation method and application of foamed nickel in-situ-supported SnO2 nanoparticles doped graphite carbon composite material
CN109301249A
Layered double-metal hydroxide room temperature catalyst as well as preparation method and application thereof
CN116786125A
Lighting device for vehicle
KR1020230027423A
P-n heterojunction composite material supported on surface of nickel foam, preparation method therefor and use thereof
WO2021212923A1
